Inheritance of Soybean Pod Number Trait on Acid Soil - Heru Kuswantoro; Nur Basuki; D. M. Arsyad (AGRIVITA, Journal of Agricultural Science, 2011)
Al-toxicity stressed soybean will show its tolerance response by changing pod number per plant. Hence, Al-toxicity tolerance of soybean can be predicted using that character. The objective of the research was to study inheritance of pod number trait of soybean on acid soil. Development of base population was carried out by crossing the genotypes of W3898- 14-3 with MLGG 0583 and MLGG 0709 from March 2002 to January 2003. Then, from March to June 2003, 13 populations resulting from soybean base population were grown on Pulung Kencana, Tulang Bawang, Lampung, where the soil is Ultisol with Al saturity of 32.84%. The design was randomized completely block design with three replications. The space was 40 x 15 cm, one plant per hill. Results showed that based on pod number per plant, soybean tolerance was polygenically controlled, where the gene action was additive and there was no allelic and non-allelic interaction genes. Narrow sense heritability was low, while broad sense heritability was classified as high. Keywords : Al-toxicity, gene action, heritability, pod number trait, soybean